Climate change impact on daily pan evaporation - Támas Weidinger; István Matyasovszky; István Bogárdi; Judit Bartholy (Meteorologische Zeitschrift, 1995)
A methodology is developed and applied to the region of Lake Balaton as a case study to estimate the space-time distribution of daily pan evaporation under climate change. The approach is based on the analysis of the Markov properties of atmospheric circulation pattern (CP) types and a stochastic linkage between daily CP types (700 hPa) and daily pan evaporation. Historical data and the General Circulation Model (GCM) output of daily CP corresponding to 1xCO2 and 2xCO2 scenarios are considered. The relationship between spatially averaged geopotential height of the 700 hPa surface within each CP type and daily pan evaporation is described by a nonparametric regression technique. The time series of daily pan evaporation corresponding to each of these cases are simulated and their statistical properties are compared using two different classifications of CPs. Under the moderate continental climate of the region of Lake Balaton, the space-time response of daily pan evaporation (and lake evaporation) to global climate change is variable. In general, a warmer climate obtained from the T21 version of the GCM of the Max Planck Institute results in a 3-4 % increase of pan evaporation during the summer season.